Risk of tuberculosis in patients with immune-mediated diseases on biological therapies: a population-based study in a tuberculosis endemic region. (14th December 2018) - Wang, Xing; Wong, Sunny H; Wang, Xian-Song; Tang, Whitney; Liu, Chang-Qin; Niamul, Gani; Wu, Bin; Tam, Lai-Shan; Wu, Justin C Y; Chan, Francis K L; Sung, Joseph J Y; Ng, Siew C
Abstract: Objective: Real-world epidemiological data on the risk of tuberculosis (TB) in patients with immune-mediated diseases treated with biologics are scarce in TB endemic areas. We investigated the incidence of TB in a population-based setting and stratified the risk of TB among different biological therapies. Methods: We collected medical data from a territory-wide computerized database in Hong Kong. We reported the incidence of TB in patients treated with various classes of biologics, and calculated standardized incidence ratio by comparing with the general population. Subgroup analyses were performed based on disease subtypes and biological drugs. Results: Among 2485 subjects with immune-mediated diseases (82.5% rheumatology diseases; 10.6% IBD; 6.9% dermatology diseases), 54 subjects developed active TB during 6921 person-years of follow-up. The mean age (±s.d.) was 43 (14) years, and the median follow-up duration was 24.9 months (interquartile range 4.9–45.0). The overall standardized incidence ratio of TB was 10.91 (95% CI 8.00–13.82), and patients treated with infliximab had a nearly 26 times increased risk of TB compared with the general population (standardized incidence ratio 25.95; 95% CI 17.23–34.67). The risk of TB with TNF inhibitor was higher than with a non-TNF biologic (hazard ratio 4.34; 95% CI 1.31–14.39), while the risk of infliximab was higher than etanercept and adalimumab (hazard ratio: 4.10 and 2.08, respectively). Conclusion: The risk of TB is much higher in patients with immune-mediated diseases on biological therapy compared with the general population, and infliximab is associated with the highest risk of TB among the biologics analysed.